Kekuatan Digital Forensik dalam Mengungkap Tindak Pidana Cyber Crime : Studi Kasus : Hacker Ilegal Akses Pembayaran Kereta Commuter Indonesia (KCI)) - Ira Irmansyah (Badan Penerbit STIEPARI Press, 2024)
This research discusses the strategic role of digital forensics in uncovering cyber crime with a case study of the hacking of the Multi Trip Card (KMT) payment system owned by the Indonesian Commuter Train (KCI). This case involves perpetrators who use illegal software to manipulate digital balances on KMT cards, so that they only pay a small amount but get a large balance. This phenomenon causes financial losses as well as threats to public trust in electronic payment systems. The research method used is qualitative descriptive with a case study approach. The analysis was carried out on various digital traces, ranging from server logs, transaction records, to metadata that becomes electronic evidence. Digital forensics plays a role in the process of identifying, collecting, securing and analyzing data to ensure the validity of evidence. The findings suggest that electronic evidence can have legal force if obtained through lawful procedures, for example by using chains of custody and standardized forensic analysis methods. In addition, this study highlights the weakness of digital security systems that are a loophole for cybercriminals. Digital forensics is not only important in the investigation stage, but also as a means of security evaluation to anticipate similar crimes. Law enforcement against cases like this requires collaboration between law enforcement officials, forensic experts, digital service providers, and regulators. The application of the latest security technologies, such as data encryption, anomaly detection systems, and periodic audits, is considered to be able to minimize the potential for manipulation. The implication of this research is the need to increase awareness, strengthen regulations, and technological innovation in dealing with the development of cyber crime. Digital forensics is proving to be a vital instrument that not only supports investigations, but also maintains the integrity of digital systems.